Capabilities assessment for working bodies of rotary snowblowers through design and technological parameters study - D. S. Aleshkov; P. A. Korchagin; I. A. Teterina; E. V. Khirianov (Вестник СибАДИ)
Introduction. At the initial stages of designing snow blower feeders, it is necessary to have relatively simple ratios on the basis of which one can judge their efficiency and their potential. The presence of such indicators makes it possible to reasonably choose the design scheme, geometric and kinematic parameters of the working bodies of rotary snowplows. The solution of such problems, in turn, can significantly reduce the time for designing machines and their working bodies. Thus, the main goal of this study is to assess the possibility of substantiating the effectiveness of design solutions for snow blowers in the early stages of design. Methods and materials. To achieve this goal, such tasks as the substantiation of the indicators on the basis of which the effectiveness will be assessed, description of the mechanism for obtaining their theoretical values were solved. Results. As a result of the research, analytical expressions were obtained for the volumes of snow mass cut by horizontal and vertical cutters of the rotary snowplow feeder. The time of transporting the cut snow mass has been estimated. The degree of influence of a number of design and technological parameters on the size of the cut snow mass and the time of its transportation is shown. Discussion and conclusion. The equations for the lengths of the trajectories of motion of an arbitrary point of the cutter of the feeder of a rotary snowplow are obtained for its vertical and horizontal arrangement. The equations make it possible to determine the duration of the interaction between the transported snow mass and the working equipment from the moment of its capture to the moment of its unloading. As a result of the research, the range of values was determined, in which the length of the cutting path of the snow mass for a horizontal cutter is less than the length of the cutting path for a vertical cutter.